Anatolia: Old and New Perspectives - Mellink, Machteld J.
I. Classical Trends; II. Oriental Trends; III. Present Trends: 1. The beginnings of settled village life; 2. The early stages of village and town development; 3. The chalcolithic stage; 4. The early bronze age, third millennium B.C.; 5. The middle bronze age ca. 2000-1600 B.C.; 6. The Hittites; 7. West Anatolians and Mycenaeans; 8. The end of the bronze age; 9. Postscript.